Effect of No Tillage System on Soil Fungal Community Structure of Cropland in Mollisol: A Case Study - Gao, Ming; Li, Haiyu; Li, Meng (Frontiers in Microbiology, 2022)
Conservation tillage is generally regarded as a sustainable farming system in the future. The fungal community structure has a strong response to conservation tillage. However, how the conservation tillage system affects the soil fungal community structure is slightly known. Here, using the high-throughput sequencing technology, the soil fungal community was explored under no tillage (NT) and conventional tillage (CT) in Northeast China Mollisol. The copy number of fungal genes in NT20 was significantly lower than that in other treatments. NT changed the composition of soil fungal communities at the taxonomic level of phylum and genus. The diversity indices of soil fungal community in no tillage at soil depths of 0–5 cm (NT5)were significantly higher than those in 5–20 cm (NT20). The fungal community under NT and CT could form a good cluster distribution and NT5, conventional tillage at soil depths of 0–5 cm (CT5)and 5–20 cm (CT20)had specific indicator species. Most of the potential pathogens were significantly higher in NT5 than in NT20. Tillage and soil depth could explain 64% diversity and 95% composition of fungal community, which indirectly changed the diversity and composition of fungi by using soil organic carbon, pH value, and soil bulk density. Furthermore, soil organic carbon (SOC) best explained the soil fungal community, followed by soil pH. The study indicated that the NT system had comprehensive effect on soil fungal community and SOC is the most crucial factor in determining this community.